Best Answer

First, look at the given problem. eg. (8n-3)^3. Mark the first term (8n) A then mark the second term (-3) B. Do this formula. (a+b)^3 = a^3 + 3a^2b + 3ab^2 + b^3

Q: How do you cube binomial?

Write your answer...

Submit

Still have questions?

Related questions

Consider a binomial (a+b). The cube of the binomial is given as =(a+b)3 =a3 + 3a2b + 3ab2 + b3.

99x99x99

To calculate the cube of a binomial, you can multiply the binomial with itself first (to get the square), then multiply the square with the original binomial (to get the cube). Since cubing a binomial is quite common, you can also use the formula: (a+b)3 = a3 + 3a2b + 3ab2 + b3 ... replacing "a" and "b" by the parts of your binomial, and doing the calculations (raising to the third power, for example).

jb+++u

(8m+6)

that;s so simple . try it

(a + b)3 = a3 + 3a2b + 3ab2 + b3

The cube of a binomial is the cube of two terms separated by an addition or subtraction sign, such as (2a + 3b) or (ab - cd).For example, (2x - 5y)3 = 8x3 - 40x2y + 50xy2 - 20x2y + 100xy2 - 125y3.The detailed method of expanding this binomial is : (2x - 5y)3 = (2x - 5y)(2x - 5y)(2x - 5y) = (4x2 - 20xy + 25y2)(2x - 5y) = 8x3 - 40x2y + 50xy2 - 20x2y + 100xy2 - 125y3

The special products include: difference of the two same terms square of a binomial cube of a binomial square of a multinomial (a+b) (a^2-ab+b^2) (a-b) (a^2+ab+b^2)

The special products include: difference of the two same terms square of a binomial cube of a binomial square of a multinomial (a+b) (a^2-ab+b^2) (a-b) (a^2+ab+b^2)

Binomial. Binomial. Binomial. Binomial.

STEPS : FIRST TERM = the cube of the first term SECOND TERM=three times the product of the squareof first term and second term THIRD TERM=three times the product of first term and square of second term FOURTH TERM=THE CUBE OF THE LAST TERM ..